2007
DOI: 10.1016/s0929-6646(08)60021-2
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Therapeutic Response to Beta-blockers in Patients with Heart Failure in Taiwan

Abstract: We demonstrated the therapeutic effects of beta-blockers in Taiwanese HF patients with a dose lower than what has been reported in Western people. Moreover, patients with the etiology of dilated cardiomyopathy or lower baseline LVEF predicted a greater LVEF improvement. The beta1-adrenoceptor gene polymorphisms were not responsible for the difference in sensitivity to beta-blockers in this Taiwanese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
1
2
0
1
Order By: Relevance
“…Our results also seem to be different from the belief that the Arg allele is more cardio‐stimulatory than the Gly allele. A number of previous studies indicated that the effects of the polymorphism on Chinese or Japanese subjects are negative in terms of normal cardiovascular functions, cardiovascular diseases or therapeutic response to beta‐blockers 27,29–32 . Our findings in the present study seem to be consistent with these published works.…”
Section: Discussionsupporting
confidence: 93%
“…Our results also seem to be different from the belief that the Arg allele is more cardio‐stimulatory than the Gly allele. A number of previous studies indicated that the effects of the polymorphism on Chinese or Japanese subjects are negative in terms of normal cardiovascular functions, cardiovascular diseases or therapeutic response to beta‐blockers 27,29–32 . Our findings in the present study seem to be consistent with these published works.…”
Section: Discussionsupporting
confidence: 93%
“…Tolerant doses to NSBBs in different ethnic groups may have resulted in no remarkable effect on HCC prevention in this study. Because the Asian population requires lower doses of NSBBs to reach the target blood pressure and heart rate than does the Caucasian population, the dose used on each day in this study was lower than that used in studies of the Caucasian population (Zhou et al, 1989;Hu et al, 2007). NSBB use appeared to benefit HCC prevention in the Caucasian population more than in the Asian population (Kim et al, 2012;Nkontchou et al, 2012;Herrera et al, 2016;Yeh et al, 2019;Wijarnpreecha et al, 2021).…”
Section: Discussionmentioning
confidence: 83%
“…No study has examined the association between NSBBs and the incidence of HCC in patients with CHB who may develop HCC without cirrhosis and have a lower risk of HCC than do patients with existing cirrhosis. In addition, most studies have recruited a Western population, whose aetiology of HCC and responses to NSBBs differ from those of the East Asian population (Zhou et al, 1989;Hu et al, 2007). Therefore, this study investigated the association between NSBB use and the incidence of HCC in patients with CHB in the absence of liver cirrhosis and decompensation.…”
Section: Introductionmentioning
confidence: 99%
“…Auch im Rahmen einer Studie an chinesischen Herzinsuffizienz-Patienten konnte zwischen den verschiedenen Varianten kein Unterschied hinsichtlich der Empfindlichkeit auf Betablocker-Therapie gefunden werden (Hu et al 2007).…”
Section: Bedeutung Im Zusammenhang Mit Betablocker-therapieunclassified